How local leaders view transparency and local autonomy in humanitarian aid distribution: Evidence from Mali - Bleck, Jaimie; Carrillo, Lucia; Gottlieb, Jessica; Guindo, Sidiki; Kosec, Katrina; Kyle, Jordan; Soumano, Moumouni (International Food Policy Research Institute, 2025)
Recognizing the pivotal role local governance plays in crisis response and the diversity of local conditions even within a single country context, this article examines variation in preferences over humanitarian aid delivery among local leaders in Mali. Drawing on qualitative fieldwork and a survey of 2,919 local leaders across the country, we investigate leaders’ preferences over two key dimensions of aid governance: local autonomy over targeting and distribution and transparency over aid delivery. Using aid profile vignettes to elicit preferences over these attributes, we find that leaders generally favor approaches that combine both greater local control and greater transparency, viewing transparency as complementary to autonomy rather than constraining. Preferences, however, vary by leaders’ position and by context: outsiders to aid governance demand more transparency, and leaders’ relative trust in local aid committees versus donors predicts preferences for autonomy. Leaders in conflict-affected villages place greater value on autonomy and less on transparency, highlighting how insecurity reshapes aid preferences in fragile settings.